VULPIA (GRAMINEAE) IN MALESIA - Alex - Sumadijaya; Jan Frits Veldkamp (Reinwardtia, 2009)
SUMADIJAYA, A. & VELDKAMP, J. F.2009. Vulpia (Gramineae) in Malesia. Reinwardtia 12(5): 343–346.- A brief account of Vulpia (Gramineae) in Malesia is which consisting of V. bromoides and V. myuros is provided here, based on material seenprimarily by JFV in BO, K, L, CANB.